Mediterranean diet as the diet of choice for patients with chronic kidney disease. Issue 5 (2nd July 2017) - Chauveau, Philippe; Aparicio, Michel; Bellizzi, Vincenzo; Campbell, Katrina; Hong, Xu; Johansson, Lina; Kolko, Anne; Molina, Pablo; Sezer, Siren; Wanner, Christoph; ter Wee, Pieter M; Teta, Daniel; et al.
ABSTRACT: Traditional dietary management of chronic kidney disease (CKD) focuses on the quantity within the diet of energy and protein, and the restriction of single micronutrients, with little mention of dietary quality. Dietary patterns that are more plant-based, lower in meat (including processed meat), sodium and refined sugar, and have a higher content of grains and fibres are now included in multiple clinical guidelines for chronic disease prevention. The Mediterranean diet (MD) has been associated with reduced cardiovascular disease incidence in both observational and interventional studies. A wealth of evidence links MD with other beneficial effects on chronic diseases such as diabetes, obesity or cognitive health. This review examines each constituent of the classical MD and evaluates their suitability for the management of patients with CKD. We also evaluate the potential hyperkalaemia risk of increasing fruit and vegetable intake. Overall, a decrease in net endogenous acid production and increase in fibre may lead to a better control of metabolic acidosis. This, together with other putative favourable effects of MD on endothelial function, inflammation, lipid profile and blood pressure, provide mechanistic pathways to explain the observed reduced renal function decline and improved survival in CKD patients adhering to an MD.